The Sdp-SH3b2 domain contained in Lactobacillus johnsonii N6.2-derived extracellular vesicles inhibit murine norovirus replication - da Silva, Danilo R.; Sharjeel, Asra B.; Beliakoff, Reagan; Teixeira, Leandro D.; Kima, Peter E.; Jones, Melissa K.; Gonzalez, Claudio F.; Lorca, Graciela L. (Frontiers in Immunology, 2024)
The internalization of Lactobacillus johnsonii N6.2 extracellular vesicles (EVs) by cells results in a significant induction of the 2’,5’-oligoadenylate synthetase (OAS) pathway. It also induces expression of IFI44L, MX1, MX2 and DDX60. In this work, we evaluated whether the antiviral response induced by L. johnsonii N6.2-derived EVs, has an inhibitory effect on an RNA viral insult using murine norovirus (MNV-1) as the viral infection model. We found that RAW 264.7 Macrophages treated with EVs significantly decreased the levels of MNV-1 genome. These results were consistent with an increase in expression of Oas1b, Oas2, Oasl, Mx1, Mx2 and Ifi44l (6 hours post infection). Out of six proteins enriched in EVs, we found that SH3b2 domain of Sdp was the only protein effector molecule able to recapitulate the activation of the OAS pathway. In C57BL6 mice, the administration of live L. johnsonii N6.2, EVs, and Sdp-SH3b2/liposomes significantly decreased MNV-1 titers in the distal ileum, in contrast to the controls with PBS and liposomes alone that did not affect MNV-1. These results establish that the SH3b2 domain of Sdp, which is enriched in L. johnsonii derived EVs, is an effector molecule in EVs that can orchestrate the control of viral infections in vivo.